Understanding the association between condom use at first and most recent sexual intercourse: An assessment of normative, calculative, and habitual explanations - Štulhofer, Aleksandar (Array, 2010)
The aim of this study was to provide a better understanding of the likely mechanisms underlying regular condom use. In 2009, 1145 sexually active individuals aged 18e65 years were surveyed online, after being recruited via an e-mail message circulated at a large Croatian university and posted on various social networking websites. Participants’ mean age was 28.1 years (SD = 8.01). Women constituted a slight majority of the sample (51.6%). The research questions e whether the frequently observed association between condom use at first and most recent sexual intercourse could be best predicted by (a) norm-oriented behavior ; (b) calculative decision-making ; or (c) habit formation e were tested using multiple logistic regression. Only the calculative and habitual motivational determinants of condom use were significant predictors. Unlike calculative use, which decreased the odds of condoms being used at both occasions, habitual use, as expected, increased the odds of condom use. In addition, the habitual modality of condom use significantly predicted consistent condom use with both casual and steady sexual partners. Age, being in a relationship, and the number of lifetime sexual partners were negatively associated with habitual condom use. The finding that habit plays a substantial role in consistent condom use suggests the need for further exploration of personality and relational factors associated with the initiation of habitual condom use.